2022
DOI: 10.1101/2022.07.14.500016
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

In-line swimming dynamics revealed by fish interacting with a robotic mechanism

Abstract: Schooling in fish is linked to a number of factors such as increased foraging success, predator avoidance, and social interactions. In addition, a prevailing hypothesis is that swimming in groups provides energetic benefits through hydrodynamic interactions. Thrust wakes are frequently occurring flow structures in fish schools as they are shed behind swimming fish. Despite increased flow speeds in these wakes, recent modelling work has suggested that swimming directly in-line behind an individual may lead to i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…We note that the wavelength (as a fraction of the body length) can be computed from the phase lag, and we report this metric in the supplementary data ( Thandiackal and Lauder, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…We note that the wavelength (as a fraction of the body length) can be computed from the phase lag, and we report this metric in the supplementary data ( Thandiackal and Lauder, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…Schooling refers to the coordinated swimming of fish in close proximity in crystallized spatial formations, as exhibited by most fish species (Filella, Nadal, Sire, Kanso, & Eloy, 2018;Kalueff et al, 2013;Shaw, 1978). Different patterns of fish schooling that are often shown to emerge include side-by-side (phalanx), in-line and staggered (diamond) formations (Daghooghi and Borazjani, 2015;Hemelrijk et al, 2015;Oza, Ristroph, & Shelley, 2019;Park & Sung, 2018;Thandiackal & Lauder, 2022;Weihs, 1973). One approach to explain schooling is based on the premise of collective energy savings so that fish arrange their positions with respect to their neighbours in an attempt to reduce their swimming costs (Ashraf et al, 2017;Liao, Beal, Lauder, & Triantafyllou, 2003a;Maertens et al, 2017;Marras et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Towards this aim, we focus on a fish pair as a minimalistic instance of a school. Experimental studies involving pairs of live fish have shown evidence for specific schooling configurations, such as side-byside (Ashraf, Godoy-Diana, Halloy, Collignon, & Thiria, 2016;Chicoli et al, 2014) as well as in-line (Thandiackal & Lauder, 2022) configurations, when swimming against a flow. Recent work by De Bie, Flow E31-3 Manes, and Kemp (2020) has further shown that pairs of fish tend to swim in-line in placid water, side-by-side in a high speed flow, and without any identifiable pattern in a low-speed flow.…”
Section: Introductionmentioning
confidence: 99%